Informal task‐sharing practices in inpatient newborn settings in a low‐income setting—A task analysis approach. Issue 3 (27th February 2020) - Omondi, Gregory B.; Murphy, Georgina A. V.; Jackson, Debra; Brownie, Sharon; English, Mike; Gathara, David
Abstract: Aim: To describe the complexity and criticality of neonatal nursing tasks and existing task‐sharing practices to identify tasks that might be safely shared in inpatient neonatal settings. Design: We conducted a cross‐sectional study in a large geographically dispersed sample using the STROBE guidelines. Methods: We used a task analysis approach to describe the complexity/criticality of neonatal nursing tasks and to explore the nature of task sharing using data from structured, self‐administered questionnaires. Data was collected between 26th April and 22nd August 2017. Results: Thirty‐two facilities were surveyed between 26th April and 22nd August, 2017. Nearly half (42%, 6/14) of the "moderately critical" and "not critical" (41%, 5/11) tasks were ranked as consuming most of the nurses' time and reported as shared with mothers respectively. Most tasks were reported as shared in the public sector than in the private‐not‐for‐profit facilities. This may largely be a response to inadequate nurse staffing, as such, there may be space for considering the future role of health care assistants.